Let’s Take A Walk: Exploring the Impact of an Inclusive Walking Program on the Physical and Mental Health of Adults with Intellectual Disability - Jones, Jennifer L.; Gallus, Kami L.; Emerson, Sam R.; Sciarrillo, Christina M.; Waldrop, Tia C. (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: People with intellectual disabilities experience health disparities and poorer health outcomes than people without disabilities. Increased physical activity has been found to reduce the impact of chronic health conditions among people with intellectual disabilities. Method: The current study explored the impact of an inclusive walking program on the physical and mental health of adults with intellectual disabilities. Let’s Take A Walk paired adults with intellectual disabilities, hereafter referred to as Community Walkers (n = 27), with college students to walk around a college campus twice a week for 45 minutes across 10 weeks. Data on mental health outcomes, specifically depression and anxiety, were collected from 24 Community Walkers across four-time points (pre-, mid-, post-, and 3-months following intervention), and data on physical health outcomes were collected across two-time points (pre- and post-intervention). Results: Community Walkers reported significant decreases in both depression and anxiety from pre to post-implementation. Particularly promising was clinically significant decreases in anxiety symptoms over the 10-week program. No differences were noted on Community Walkers’ measures of physical health. Conclusion: Inclusive walking programs are a valuable and promising mechanism for building social connections and inclusion and improving mental health for adults with intellectual disabilities.